2023
DOI: 10.1021/acs.jpca.2c08619
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Valence Shell Excitation by Electron Impact in CCl4

Abstract: This paper reports a theoretical study of valence shell excitation in CCl 4 by high-energy electron impact. Generalized oscillator strengths are calculated for the molecule at the equation-of-motion coupled-cluster singles and doubles level. To elucidate the influence of nuclear dynamics on electron excitation cross-sections, the effects of molecular vibration are included in the calculation. Based on a comparison with recent experimental data, several reassignments of spectral features are made, and it is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…More exactly, Palmer et al [15] yielded higher oscillator strengths than the experimental data while Zhan et al [18] predicted much lower values. The ignored vibronic effects might be the reason for the difference between the observations and calculations [49][50][51].…”
Section: Resultsmentioning
confidence: 93%
“…More exactly, Palmer et al [15] yielded higher oscillator strengths than the experimental data while Zhan et al [18] predicted much lower values. The ignored vibronic effects might be the reason for the difference between the observations and calculations [49][50][51].…”
Section: Resultsmentioning
confidence: 93%
“…It has been demonstrated that such a theoretical calculation procedure can successfully elucidate the momentum transfer dependence behaviors of GOSs for many molecules. [2,4,[6][7][8][9] In this work, the GOSs of the 1 A 2 ←− X1 A 1 transitions of H 2 O and D 2 O were calculated by using Gaussian16 software, to elucidate the influence of the vibronic effect on this transition character. The vibrational normal coordinates and vibrational frequencies of H 2 O and D 2 O were calculated using 053401-2 the basis set of aug-cc-pVTZ [34,35] at the treatment level of the second-order Mφ ller-Plesset perturbation theory (MP2).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Although electron collisional excitation cross sections for the low electronic states of H 2 O have been extensively studied both theoretically [17][18][19][20] and experimentally, [17,[21][22][23][24][25][26] the influence of the vibronic effect on them has not been considered while it has great influence on other molecules. [1][2][3][4][5][6][7][8][9] This paper focuses on the vibronic effect and isotopic effects of the dipole-forbidden transition 1 A 2 of H 2 O and D 2 O, and according to the previous investigations, [1][2][3][4][5][6][7][8][9] the vibronic effect on this transition should be prominent. The 1 A 2 states of H 2 O and D 2 O were noticed in the electron energy loss spectra at the impact electron energies of 100 eV-200 eV, [25] 300 eV-500 eV, [27] and 1500 eV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations